Systematic review of religious affiliations and beliefs as correlates of public attitudes toward capital punishment - Rade, Candalyn B. (Criminal justice studies, 2017)
Religious reasons are frequently described as considerations that shape support for or opposition to capital punishment; however, there are many inconsistencies in the literature. This study represents a systematic review of the extant research on religious affiliations and beliefs as correlates of public attitudes toward capital punishment. Searches conducted in five databases identified 33 articles, representing 97,570 respondents. Results revealed that people belonging to Protestant affiliations and with negative images of God were more likely to support capital punishment. People possessing positive images of God and with strong beliefs in compassion were less likely to support capital punishment. The religious correlates commonly assessed in the extant literature, such as fundamentalism, are not significant correlates of attitudes toward capital punishment. Findings also revealed that the predominance of research examined Christian religious affiliations, to the exclusion of other common affiliations, such as Buddhist or Islamic affiliations. Taken together, findings suggest that compared to affiliations, religious beliefs better explain attitudes toward capital punishment. Further research is needed to investigate the ways religious correlates influence death qualified jury selection and capital sentencing decisions. An increased understanding of the nuanced relationship between religion and capital punishment attitudes can better inform capital punishment policy and practice.